Metallic plasmons significantly boosted visible-light photocatalytic hydrogen evolution from water splitting. Issue 1 (6th December 2022) - Ullah, Ikram; Ling, Cong; Li, Jing-Han; Lu, Xiao-Jie; Li, Chenchuang; Yang, Zhengkun; Qian, Xiao-Jun; Wang, Gang; Xu, An-Wu
Abstract : Surface plasmon resonance (SPR) of Ni nanoparticles has been studied to promote the generation of hot electrons, charge transfer and separation over g-C3 N4 /Ni@C plasmonic photocatalysts, resulting in boosted visible-light photocatalytic H2 evolution from water splitting. Abstract : Under visible-light irradiation, graphitic carbon nitride (g-C3 N4 ) is considered a favorable photocatalyst for hydrogen (H2 ) production from water splitting. However, the poor H2 production and fast recombination rate of charge carriers prevent its practical applications. Therefore, the integration of g-C3 H4 with suitable plasmonic materials to develop a nanocomposite photocatalyst is worthwhile for enhancing H2 evolution. Herein, a highly efficient g-C3 N4 /Ni@N-doped C (termed as CN/Ni@C) plasmonic photocatalyst is developed by the combination of g-C3 N4 and nickel supported on nitrogen-doped carbon (Ni@C) for H2 production from water splitting. The results show that photocatalytic performance is enhanced by Ni metallic plasmons over the CN/Ni@C nanocomposite. The optimized CN/Ni@C-1 (1 wt% Ni@C loading) plasmonic heterojunction achieves an efficient H2 evolution rate of 56.67 μmol h −1, which is 4-fold higher than that of bare g-C3 N4 (13.55 μmol h −1 ) with an apparent quantum yield (AQY) of 5.20% under visible-light irradiation ( λ ≥ 420 nm). This improved performance is associated with the efficient charge separation, charge transfer, and surface plasmon resonance (SPR) effect of metallic Ni nanoparticles. Additionally, the optimal CN/Ni@C-1 plasmonic heterojunction exhibits excellent photocatalytic stability toward H2 generation. We believe that this study will open the door to constructing and developing other plasmonic material decorated g-C3 N4 photocatalysts for potential applications in sustainable and renewable energy.